The Wellbeing Thermometer in Patients with Colorectal Cancer: A Validation Study - Marios Adamou; Okezie Uche-Ikonne; Konstantinos Kamposioras (Diseases)
Background: Wellbeing is a valuable outcome with benefits for patients and the wider healthcare system. Different instruments are available to measure wellbeing; however, each has its own limitations. Existing wellbeing models focus mostly on a single aspect (e.g., social). The Wellbeing Thermometer (WbT) was developed based on a more holistic framework for wellbeing. Objective: The aim of this research was to validate the WbT on patients receiving treatments using a sample of patients with colorectal cancer in England. Methods: A survey, including GAD-7, PHQ-9, WHO-5, and WbT, was administered to two independent cohorts of adult patients diagnosed with colorectal cancer. The WbT consists of 25 questions/items: 5 for each domain of health, thoughts, emotions, spiritual, and social. We investigated the psychometric properties of the WbT to characterize item difficulty, discrimination, and reliability. Pearson’s correlation coefficient was used to compare WbT scores to those from other validated tools. A multivariable logistic model explored associations between WbT domains and other validated tools. Results: Cronbach’s alpha for WbT was 0.872 (95% confidence interval: 0.829–0.902), indicating good internal consistency. The item difficulty for WbT showed low scores for questions 6 (0.39) and 9 (0.49) and high scores for the other items. Item 3 in the health subgroup indicated weak discrimination towards the health item score (r = 0.35) and no discrimination towards the total score (r = 0.03). Item 1 in the spiritual subgroup showed weak discrimination towards the spiritual item score (r = 0.37). The WbT showed moderate to strong correlation with all other validated tools (r range: GAD-7, −0.49 to −0.77; PHQ-9, −0.69 to −0.83; WHO-5, 0.66 to 0.85). For Cohort 1, the WbT thought domain was associated with GAD-7 (p = 0.004) and WHO-5 (p = 0.002), and the health domain was associated with PHQ-9 (p = 0.014). For Cohort 2, the WbT thought domain was associated with GAD-7 (p = 0.02), the health domain was associated with WHO-5 (p = 0.02), and the emotion domain was associated with WHO-5 (p = 0.02). Conclusions: The WbT is a valid tool for assessing wellbeing in patients with colorectal cancer. The WbT may be a useful addition to both clinical practice and future research and may help shed light on a new area with regards to patients with cancer, specifically how they feel and function. This will ultimately increase wellbeing and reduce suffering.